2018
DOI: 10.2147/ceor.s140208
|View full text |Cite
|
Sign up to set email alerts
|

The economic and clinical burden of early versus late initiation of celecoxib among patients with osteoarthritis

Abstract: ObjectiveThis study aimed to evaluate the characteristics associated with early versus late initiation of celecoxib treatment after osteoarthritis (OA) diagnosis and whether economic and safety outcomes differ between patients with early versus late initiation of celecoxib.MethodsAdults (≥18 years) with a confirmed OA diagnosis (International Classification of Diseases, 9th Edition, Clinical Modifications code: 715.XX), ≥12 months of continuous pre- and post-index enrollment, and ≥1 post-index claim for celeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…OA-related costs were between $5000 and $6000 per patient year (PPY), within the range of previously reported costs ($5000-$7000 per patient year), [24][25][26] and were higher in persistent celecoxib patients compared with those who switched to a generic NSAID. However, over 45% of OA-related costs for persistent patients were drug-related versus only 19% in patients that switched to NSAIDs.…”
Section: Discussionsupporting
confidence: 76%
“…OA-related costs were between $5000 and $6000 per patient year (PPY), within the range of previously reported costs ($5000-$7000 per patient year), [24][25][26] and were higher in persistent celecoxib patients compared with those who switched to a generic NSAID. However, over 45% of OA-related costs for persistent patients were drug-related versus only 19% in patients that switched to NSAIDs.…”
Section: Discussionsupporting
confidence: 76%
“…23,26,49 The DCE sample was also representative in terms of the sites of osteoarthritis occurrence; many participants had osteoarthritis at multiple sites, with knee osteoarthritis being the most common, followed by hip osteoarthritis and then hand osteoarthritis. [50][51][52][53] Overall, the results on the importance of symptom relief and risks of serious events are in line with the results of a previous DCE on osteoarthritis medication by Hauber et al 18 The DCE by Hauber et al was based on symptom relief 1 h after taking osteoarthritis medication and assumed that the treatment effect did not degrade over time. Both studies found that stiffness was relatively unimportant.…”
Section: Comparison With Existing Literaturesupporting
confidence: 72%
“…23,26,49 The DCE sample was also representative in terms of the sites of osteoarthritis occurrence; many participants had osteoarthritis at multiple sites, with knee osteoarthritis being the most common, followed by hip osteoarthritis and then hand osteoarthritis. 5053…”
Section: Discussionmentioning
confidence: 99%
“…In another microsimulation study, a diet and exercise programme in addition to treatment in overweight and obese patients with knee OA showed ICERs of $34,100/QALY and $30,000/QALY from the health care sector perspective and the societal perspective, respectively [29]. NSAIDS, recommended by ESCEO and other scientific societies, has also been shown to be cost effective, even with OA subjects with comorbidities [30][31][32][33]. Numerous medicoeconomic evaluations are also available showing the cost-effectiveness of hyaluronic acid injection in the management of OA [34][35][36].…”
Section: Discussionmentioning
confidence: 99%